EKSPERIMENTASI MODEL PEMBELAJARAN PROBLEM BASED LEARNING DAN KOOPERATIF TIPE SNOWBALL THROWING DITINJAU DARI GAYA BELAJAR SISWA - Safa’udin, Muhamad; Budiyono, Budiyono; Sari Saputro, Dewi Retno (Jurnal Pembelajaran Matematika, 2015)
Abstract: The objective of this research was to investigate the effect of the learning models on learning achievement viewed from learning style types of the students. The learning models compared were PBL, ST, and direct learning. The type of the research was quasi-experimental research with 3x3 factorial design. The population of this research was the students in grade VIII junior high school in Nganjuk City on academic year of 2014/2015. The size of the sample was 274 students, which was taken by using stratified cluster random sampling technique. The instruments used for data collection were learning style questionnaire and mathematics achievement test. The hypothesis test used unbalance two ways analysis of variance. The results of the research were as follow. (1) Mathematics achievement of students taught by Problem Based Learning and Snowball Throwing gave better than they taught by direct learning, and mathematics achievement of students taught by Problem Based Learning and Snowball Throwing was produce the same learning achievement (2) The learning styles of visual, auditory or kinesthetic was not have an influence on learning achievement. (3) In each learning model, the students with the visual, auditory, and kinesthetic learning styles have an equal learning achievement in mathematics; (4) In each learning style, mathematics achievement of students taught by Problem Based Learning provide the same learning achievement with cooperative Throwing Snowball, and mathematics achievement of students taught by Problem Based Learning and Snowball Throwing was better than they taught by direct learning.Keywords: Problem Based Learning, Snowball Throwing, Direct Learning, Learning Style and Achievement.